Keresahan Rhoma Irama terhadap Peran Perempuan di Sektor Publik Kajian terhadap Lirik Lagu “Emansipasi Wanita” - Moh Muzakka (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
The purpose of this study is to find Rhoma Irama's views on the role of women in the public sector in the lyrics of the song he wrote in the 1980s, namely